Threats, Risks and Sustainability $1 (BAnswers by Spaces - Schrogl, Kai-Uwe.; Mathieu, Charlotte; Lukaszczyk, Agnieszka; SpringerLink (Online service) (Vienna : Springer Vienna, 2009)
Development is challenged by, at least until 2050, a strong population, more severe environmental strains, growing mobility, and dwindling energy resources. All these factors will lead to serious consequences for humankind. Inadequate agricultural resources, water supply and non renewable energy sources, epidemics, climate change, and natural disasters will further heavily impact human life. The European Space Policy Institute (ESPI) sheds a new light on threats, risks and sustainability by combining approaches from various disciplines. It analyzes what could be the contribution of space tools to predict, manage and mitigate those threats. It aims at demonstrating that space is not a niche but has become an overarching tool in solving today$1 (Bs problems.s
Setting the Stage -- Knowledge -- Environment -- Resources -- Energy -- Mobility -- Security -- Conclusions and Recommendations.
Keywords: Engineering; Climate change; Aerospace engineering; Astronautics; Engineering; Aerospace Technology and Astronautics; Climate Change/Climate Change Impacts; Electronic books